An Explicit–Implicit Spectral Element Scheme for the Nonlinear Space Fractional Schrödinger Equation - Zeting Liu; Baoli Yin; Yang Liu (Fractal and Fractional, 2023)
In this paper, we solve the space fractional nonlinear Schrödinger equation (SFNSE) by developing an explicit–implicit spectral element scheme, which is formulated based on the Legendre spectral element approximation in space and the Crank–Nicolson leap frog (CNLF) difference discretization in time. Both mass and energy conservative properties are discussed for the spectral element scheme. Numerical stability and convergence of the scheme are proved. Numerical experiments are performed to confirm the high accuracy and efficiency of the proposed numerical scheme.